Characterization of the Sweet Taste Receptor Tas1r2 from an Old World Monkey Species Rhesus Monkey and Species-Dependent Activation of the Monomeric Receptor by an Intense Sweetener Perillartine - Cai, Chenggu (PLoS One, 2016)
Sweet state is a basic physiological sensation of humans and other mammals which is mediated by the broadly acting sweet taste receptor-the heterodimer of Tas1r2 (taste receptor type 1 member 2) and Tas1r3 (taste receptor type 1 member 3). Various sweeteners interact with either Tas1r2 or Tas1r3 and then activate the receptor. In this study, we cloned, expressed and functionally characterized the taste receptor Tas1r2 from a species of Old World monkeys, the rhesus monkey. Paired with the human TAS1R3, it was shown that the rhesus monkey Tas1r2 could respond to natural sugars, amino acids and their derivates. Furthermore, similar to human TAS1R2, rhesus monkey Tas1r2 could respond to artificial sweeteners and sweet-tasting proteins. However, the responses induced by rhesus monkey Tas1r2 could not be inhibited by the sweet inhibitor amiloride. Moreover, we found a species-dependent activation of the Tas1r2 monomeric receptors of human, rhesus monkey and squirrel monkey but not mouse by an intense sweetener perillartine. Molecular modeling and sequence analysis indicate that the receptor has the conserved domains and ligand-specific interactive residues, which have been identified in the characterized sweet taste receptors up to now. This is the first report of the functional characterization of sweet taste receptors from an Old World monkey species.